BENTUK TINDAK TUTUR DIREKTIF GURU BAHASA INDONESIA DALAM PROSES PEMBELAJARAN DI SMP NEGERI 1 KARANG BAHAGIA - Yuli Y; Nawawi N (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
This article aims to determine the form of directive speech acts for Indonesian language teachers in the learning process at SMP Negeri 1 Karang Bahagia. In this study, primary data was collected by researchers directly, namely in the form of utterances and their context in the Indonesian language learning process which contained directive speech acts. In addition, secondary data is also used which comes from books on speech acts. This research uses listening method with tapping technique as the basic technique, and free-involved listening technique, recording technique, and note-taking technique as advanced technique. The results of this study found several types and functions of directive speech acts used in teacher speech in learning Indonesian in the 2013 curriculum at SMP Negeri 1 Karang Bahagia, namely directive command speech acts, request speech acts, asking directive speech acts, inviting directive speech acts, directive speech acts directive speech act of advising, and directive speech act of criticism.